ARTICULATE STORYLINE 3 SEBAGAI MEDIA PEMBELAJARAN IPA SEKOLAH PENGGERAK - Maysuri, Athanasia; Khotimah, Khusnul; Sukriadi, Sukriadi (Universitas Tanjungpura, 2024)
4C skills (Communication, Collaboration, Critical Thinking and Problem Solving, and Creativity and Innovation) are learned for the independent curriculum. The objectives of this study are; (1) the results of the feasibility of the educational media and (2) the responses of students and teachers to the developed educational media. The method used is the 3D-E development model or with 4 development procedures namely decide, design, develop and evaluate. The research subjects were 119 grade 5 students from 5 primary schools in Samarinda. The data collection technique used the evaluation questionnaire method, interviews and documentation. The results showed that: (1) The media was considered